A Hierarchically Porous Metal‐Organic Framework from Semirigid Ligand for Gas Adsorption. Issue 2 (13th November 2015) - Liu, Lizhen; Ye, Yingxiang; Yao, Zizhu; Zhang, Liuqin; Li, Ziyin; Wang, Lihua; Ma, Xiuling; Chen, Qian‐Huo; Zhang, Zhangjing; Xiang, Shengchang
Abstract: Hierarchically porous materials play an important role in facilitating mass transport and improving efficiency of adsorption and separation processes. In this paper, a new strategy is proposed to realize a hierarchically porous metal‐organic framework ([Cu2 (OH)(L)]·(DMF)0.8 (FJU‐11, H3 L=3, 5‐(4‐carboxybenzyloxy)benzoic acid, DMF= N, N ‐dimethylformamide) via using semi‐rigid multi‐carboxylic acids. Interestingly, FJU‐11 possesses the large adsorption capacities and small isosteric heats toward CO2 . The column breakthrough experiment forFJU‐11 highlights its potential application in the separation of the flue gas. Abstract : A new strategy is proposed to construct a hierarchically porous metal‐organic framework via using a multiple‐branched semirigid ligand.